STRATEGI ADAPTASI KORBAN BULYING TERHADAP PERILAKU SISWA DI SMAN 1 KEBOMAS - Sakiman Doko, Stephanus Yanuar (Paradigma, 2021)
Bullying is the act of a person or group that aims to hurt both verbally and non-verbally. The victim is under intense mental stress. He will always remember that event. so that they become afraid and traumatized. Then what is the survival strategy for victims of bullying in this high school?. for the method used is qualitative. because here the researcher will explain descriptively and see what the bullying phenomenon is like at school. for the theoretical study used is Dramaturgy in Adaptation of Bullying (Erving Goffman)